Cone Crusher Machine Maintenance Analysis Using Overall Equipment Effectiveness (OEE) and Six Big Losses Method to Improve Machine Effectiveness at PT Selo Agung - Andhika Ramadhani Ananta Irianto; Muhammad Ihsan; Indra Gumelar (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
PT Selo Agung is a company engaged in andesite stone mining located in Plered, Purwakarta Regency, West Java. Its cone crusher machine plays a vital role in crushing andesite stone into construction material, but its performance is frequently hindered by component failures and suboptimal maintenance activities, resulting in high downtime and disrupted production. This study aims to analyze the effectiveness of the cone crusher machine using the Overall Equipment Effectiveness (OEE) method, identify the factors causing the decline in production effectiveness through Six Big Losses calculation, and propose improvements to enhance machine effectiveness. Historical data from February 2025 to January 2026 were processed by calculating Availability, Performance Efficiency, and Quality Ratio, followed by Six Big Losses analysis, a fishbone diagram, and improvement proposals using the 5W+1H method. The results show that the average OEE value of the cone crusher machine was only 56.10%, far below the JIPM world-class standard of 85%, falling into the Unacceptable category. Availability at 67.86% was the largest contributor to the gap, followed by Performance Efficiency at 85.14% and Quality Ratio at 97.08%. Equipment Failure (Breakdown) Losses was identified as the most dominant loss, contributing 53.08% of total losses, mainly caused by the absence of scheduled preventive maintenance. The proposed improvements include implementing scheduled preventive maintenance with periodic replacement of the mantle and concave, developing a written maintenance SOP, operator training, and stabilizing material supply along with regular Closed Side Setting (CSS) calibration. Consistent long-term implementation (12-18 months) of these proposals is projected to raise the OEE value from 56.10% to 83.05%, approaching the world-class standard.